Design of remote monitoring system for indoor environment parameters - Xu Jun; Yang Fan; Piao Jinning; Ma Jing (Dianzi Jishu Yingyong, 2018)
A system that can monitor indoor environmental parameters and monitor remotely is designed. Through the dust concentration sensor, temperature and humidity sensors, combustible gas sensors and pressure sensors，it detects the current environment parameters, and then the microcontroller processes the data collected using Kalman filter, to get the more stable data. On the data display side, the data is sent to the self-assembled network through the hardware part of the Wi-Fi module. The browser-side programming uses the MyEclipse development environment, uses the JavaWeb language for Wi-Fi information crawling and processing, and transfers the data to Cloud, realizing the visual system design from the data collection to the network transmission, and finally to the user remote monitoring.